Multiplex genome editing by natural transformation in Vibrio mimicus with potential application in attenuated vaccine development. Issue 92 (September 2019) - Yu, Zehui; Wang, Erlong; Geng, Yi; Wang, Kaiyu; Chen, Defang; Huang, Xiaoli; Ouyang, Ping; Zuo, Zhicai; He, Changliang; Tang, Li; Yang, Zexiao; Lai, Weimin
Abstract: Vibrio mimicus ( V. mimicus ) is a significant pathogen in freshwater catfish, though knowledge of virulence determinants and effective vaccine is lacking. Multiplex genome editing by natural transformation (MuGENT) is an easy knockout method, which has successfully used in various bacteria except for V. mimicus . Here, we found V. mimicus strain SCCF01 can uptake exogenous DNA and insert it into genome by natural transformation assay. Subsequently, we exploited this property to make five mutants (△Hem, △TS1, △TS2, △TS1△TS2, and △II), and removed the antibiotic resistance marker by Flp-recombination. Finally, all of the mutants were identified by PCR and RT-PCR. The results showed that combination of natural transformation and FLP-recombination can be applied successfully to generate targeted gene disruptions without the antibiotic resistance marker in V . mimicus. In addition, the five mutants showed mutant could be inherited after several subcultures and a 668-fold decrease in the virulence to yellow catfish ( Pelteobagrus fulvidraco ). This study provides a convenient method for the genetic manipulation of V. mimicus . It will facilitate the identification and characterization of V. mimicus virulence factors and eventually contribute to a better understanding of V. mimicus pathogenicity and development of attenuated vaccine. Highlights: Natural transformation occurred in Vibrio mimicus . Natural transformation is a rapid method to create genetic deletions in V. mimicus . Natural transformation holds potential in the development of attenuated vaccine.